2003
DOI: 10.1053/jlts.2003.50135
|View full text |Cite
|
Sign up to set email alerts
|

Serial measurements of bone density at the lumbar spine do not predict fracture risk after liver transplantation

Abstract: Bone disease has emerged as a serious and complex complication after liver transplantation. The purpose of this study is to determine risk factors for fracture and bone loss after liver transplantation. Dual-energy x-ray absorptiometry (DEXA) of the lumbar spine was performed routinely pretransplantation, 6 months posttransplantation, and at yearly intervals thereafter at our center. We followed up patients who underwent transplantation in the past 10 years and compared bone mineral density (BMD) and fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…The fracture incidence, the final and most debilitating complication of osteopathy, was very low in our study with 5.8% (8 / 136 transplanted patients). Previous publications with large cohorts of LT recipients reported fracture rates between 7.5% and 65% 1, 48–50. In agreement with other studies, the majority of our patients who showed fractures developed vertebral compression fractures and traumatic fractures of peripheral bones.…”
Section: Discussionsupporting
confidence: 92%
“…The fracture incidence, the final and most debilitating complication of osteopathy, was very low in our study with 5.8% (8 / 136 transplanted patients). Previous publications with large cohorts of LT recipients reported fracture rates between 7.5% and 65% 1, 48–50. In agreement with other studies, the majority of our patients who showed fractures developed vertebral compression fractures and traumatic fractures of peripheral bones.…”
Section: Discussionsupporting
confidence: 92%
“…Bisphosphonates act by inhibiting the apoptosis of osteoclasts and osteoblasts and are the cornerstone of antiresorptive therapy in postmenopausal and steroid‐induced osteoporosis [19]. BMD measurements are widely accepted in clinical practice to guide therapy with bisphosphonates, although it has been shown that BMD values do not accurately predict fracture risk in individuals [20]. Likewise, the utility of BMD values in predicting fracture risk in organ transplant patients is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One investigator suggested that aledronate is efficacious in preventing the natural course of bone loss associated with LT (13). However, measurements of BMD at the lumbar spine do not accurately predict the risk of fractures after LT (14). So far, no randomized, controlled study on the effect of bisphosphonate therapy for preventing fractures in LT recipients after transplantation has been published.…”
Section: Introductionmentioning
confidence: 99%